The effects of acetamiprid multigeneration stress on metabolism and physiology of Aphis glycines Matsumura (Hemiptera: Aphididae). Issue 4 (13th April 2022) - Zhang, Aonan; Xu, Ling; Liu, Ziqi; Zhang, Jiabo; Han, Lanlan; Zhao, Kuijun
Abstract: Aphis glycines Matsumura (Hemiptera: Aphididae) is a major soybean pest that often poses a serious threat to soybean production. In this study, we checked the effects of acetamiprid on redox, energy metabolism, and hormone expression in A. glycines . The LC50 and LC30 of acetamiprid were used to treat the fourth instar nymphs in each generation from F0 to F4 to measure the activity of peroxidase, pyruvate kinase, and trehalase using a microassays approach. The peroxidase activity was significantly higher than control when treated with the LC30 of acetamiprid in F2−F5 generations. The activity of pyruvate kinase was significantly higher, while trehalase activity was substantially lower than control in each generation. Besides, we monitored molting and juvenile hormone expression in soybean aphids using enzyme‐linked immunosorbent assay. The juvenile hormone titer of third instar nymphs was significantly higher in the treatment group (F1, F2, F4, and F5), while no effects were noted in the F3 generation. Taken together, the activity of peroxidase and pyruvate kinase in soybean aphid first increased to the peak and then decreased, while the trehalase activity continuously decreased in all generations following exposure to acetamiprid. The juvenile hormone titer was significantly higher, while the molting hormone titer was significantly lower in LC50 ‐treated aphids than in control. Moreover, the LC30 of acetamiprid increased the molting hormone expression in soybean aphids. These findings indicated a baseline for the effective use of acetamiprid in controlling soybean aphids. Abstract : Continuous exposure of LC50 and LC30 of acetamiprid stimulated the activity of peroxidase and pyruvate kinase of soybean aphids in each generation. Different from the former, the trehalase activity of soybean aphid decreased under acetamiprid stress. The LC50 of acetamiprid inhibited the growth of soybean aphids, while LC30 concentration accelerated the development and molting. The soybean aphid response to continuous insecticide stress might be cross‐generational.